MG-CR-TYPE SPINEL PERIDOTITES IN THE WESTERN PART OF THE CENTRAL ASIAN OROGENIC BELT (ZHELTAU MASSIF, SOUTHERN KAZAKHSTAN): THE FIRST DATA ON P-T PATHS AND PROTOLITHS - A. V. Pilitsyna; A. A. Tretyakov; T. A. Alifirova; K. E. Degtyarev (Геодинамика и тектонофизика, 2017)
Ultramafic and mafic lithologies, attributed to the orogenic terranes and formed under ultrahigh-pressure (UHP) and high-pressure (HP) conditions, have been intensively studied for the last decades. It is mainly related to a particular significance of these rocks for geodynamics, since they contain an important information on the fluid-rock interactions and element redistribution in the subduction-collision zones and could shed the light on the tectonic evolution of the studied region.